DEVELOPMENT AND OPTIMIZATION OF GASTRO-RETENTIVE FORMULATION OF HYDRALAZINE HCL (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Hydralazine hydrochloride has a half-life of 2 to 4 hours with an oral bioavailability of 26-50%. Since hydralazine has a demethylating effect on various suppressor genes, it can be used in various types of cancer to support chemotherapy. The purpose of this study was to optimize and evaluate floating tablets of hydralazine hydrochloride designed to prolong the gastric residence time and to provide controlled release of the drug for 24 h. The floating tablets of hydralazine hydrochloride were prepared by the wet granulation method. Polymers of hydroxy propyl methyl cellulose (HPMC K100M), HPMC K15M, carbopol 940 and sodium bicarbonate were used as the release retarding agents. This study investigated utility of a 3-factor, 3-level Box-Behnken design and optimization process for floating tablet of Hydralazine with 5 replicates of center points. Amount of HPMC K4 (Hydroxy Propyl Methyl cellulose), amount of sodium bicarbonate were selected as the independent variables whereas total floating time (TFT), T90, % cumulative drug release at 24 hours, and T20, Q1 were selected as dependent variables. Non-Fickian diffusion release transport was confirmed as the release mechanism for the optimized formulation and the predicted values agreed well with the experimental values. Drug excipient compatibility studies were investigated by FTIR, DSC and XRD. The produced tablets exhibited good floating time and controlled drug release over a period of 24 h. The resultant data were critically analyzed to locate the composition of optimum formulations. All predicted values of response variables of optimized formulation demonstrated close agreement with the experimental data during optimization procedure.